2011
DOI: 10.1016/j.cell.2011.06.041
|View full text |Cite|
|
Sign up to set email alerts
|

MAVS Forms Functional Prion-like Aggregates to Activate and Propagate Antiviral Innate Immune Response

Abstract: SUMMARY In response to viral infection, RIG-I–like RNA helicases bind to viral RNA and activate the mitochondrial protein MAVS, which in turn activates the transcription factors IRF3 and NF-κB to induce type-I interferons. We have previously shown that RIG-I binds to unanchored lysine-63 (K63) polyubiquitin chains and that this binding is important for MAVS activation; however, the mechanism underlying MAVS activation is not understood. Here we show that viral infection induces the formation of very large MAVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
1,041
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,070 publications
(1,119 citation statements)
references
References 38 publications
35
1,041
3
2
Order By: Relevance
“…As many receptors in the immune system cluster for effective signal transmission (17,18), clustering of MDA5 on dsRNA may facilitate recruitment of MAVS or subsequent oligomerization of MAVS, which itself was recently shown to form prion-like fibrillar structures during antiviral signaling (10). It has been proposed that recruitment of MAVS by MDA5 depends on a conformational change of MDA5 induced by ATP hydrolysis (1,10). It would be interesting to test whether ATP hydrolysis by individual MDA5 molecules within a filament recruits MAVS and promote their oligomerization through induced proximity.…”
Section: Discussionmentioning
confidence: 99%
“…As many receptors in the immune system cluster for effective signal transmission (17,18), clustering of MDA5 on dsRNA may facilitate recruitment of MAVS or subsequent oligomerization of MAVS, which itself was recently shown to form prion-like fibrillar structures during antiviral signaling (10). It has been proposed that recruitment of MAVS by MDA5 depends on a conformational change of MDA5 induced by ATP hydrolysis (1,10). It would be interesting to test whether ATP hydrolysis by individual MDA5 molecules within a filament recruits MAVS and promote their oligomerization through induced proximity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the intact tandem CARDs are essential and sufficient for signaling [9,36,37], and mammalian RIG-I mutants with a CARD deletion or CARD point mutations (T55I or S183I) all function as a dominant inhibitor in its signaling [9,11,38]. It has also been revealed in mammals that the RIG-I downstream signaling via MAVS requires the recruitment of TRIM25 and other ubiquitination enzymes to synthesize unanchored K63-linked polyubiquitin chains binding to the CARD domains [36,37,39,40]. In the present study, RIG-Ia, the insertion variant of RIG-I with additional 38-aa residues in the CARD2 domain had no direct role in the activation of type I IFN promoter or antiviral defense, although the expression level of RIG-Ia could be induced under E. tarda or SVCV infections.…”
Section: Discussionmentioning
confidence: 99%
“…Hou et al have now used this powerful in vitro system to make the remarkable discovery that MAVS forms prion-like aggregates to propagate RIG-I signaling [7]. They mixed recombinant RIG-I, mitochondria, 5′-pppRNA, ATP, and K63 ubiquitin chains (K63-Ub4), or isolated mitochondria from cells infected with Sendai virus.…”
mentioning
confidence: 99%